A new species of spiny-backed treefrog (Osteocephalus) from Central Amazonian Brazil (Amphibia: Anura: Hylidae) - Jungfer, Karl-Heinz; Verdade, Vanessa K.; Faivovich, Julián; Rodrigues, Miguel T. (Zootaxa, 2016)
A new species of treefrog of the genus Osteocephalus is described from the Rio Abacaxis, a southern tributary of the Amazonas in the state of Amazonas, Brazil. This member of the O. buckleyi group is characterized by green dorsal colouration with irregular blotches of various shades of brown, light venter with tan spots and bold dark markings on the posterior surfaces of the thighs. It can be distinguished from its closest relative, O. helenae from the same general area, by the lack of an axillary membrane, a few indistinct tubercles on the proximal segment of Finger IV and single ulnar tubercles.